STRUCTURAL AND SEMANTIC ANALYSIS OF PHRASEOLOGICAL UNITS WITH ANTHROPONYMIC COMPONENTS IN ENGLISH AND UZBEK LANGUAGES - Olimova Muslimaxon Muzaffar qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This thesis presents the structural-semantic analysis of phraseological units with anthroponymic components in English and Uzbek. The study used comparative-contrastive, semantic, structural, morphological, and linguoculturological analysis methods to study semantic similarities, differences, and equivalents between phraseological units. By comparing the two languages, the importance of anthroponymic components in a social, historical, and cultural context was revealed. New methodological approaches based on the correspondence or differentiation of phraseological units were proposed. The results of the study expand scientific knowledge in the fields of linguistics and cultural studies, demonstrating the important role of phraseological units in the relationship between language and culture.